INVOLUNTARY TREATMENT AMONG OLDER ADULTS WITH COGNITIVE IMPAIRMENT RECEIVING NURSING CARE AT HOME. (16th November 2018) - Moermans, V; Bleijlevens, M; Verbeek, H; Tan, F; Milisen, K; Hamers, J
Abstract: The application of involuntary treatment, including the use of physical restraints (e.g. belts), psychotropic drugs (e.g. inappropriate use of anti-psychotics) and non-consensual care (e.g. restricting transportation), has a negative impact on the quality of life of cognitive impaired older adults living at home and their caregivers. Research on this topic is scarce. The aim of this study is to gain insight into involuntary treatment usage among older adults with cognitive impairment receiving home nursing. This cross-sectional study, analysed data from 1194 randomly selected older adults with cognitive impairments receiving nursing care at home in Belgium. A district nurse filled out a questionnaire based on data available in patient records. The application of involuntary treatment, who request and apply it, and associated factors were assessed. Data were analysed using descriptive analyses and random intercept logistic regression. Involuntary treatment was used in 52% of the total sample. The use of involuntary treatment was associated with ADL-dependency (O.R. 1.5), cognitive impairment (O.R. 1.39) and informal caregiver burden (O.R. 1.05). Informal caregivers most often requested the use of involuntary treatment and nurses most often applied it. This study confirms that involuntary treatment is common in home nursing and a multifactorial approach (including policy, education, consultation and alternatives) is needed to prevent and reduce it. Whenever caregivers have the skills and knowledge about alternative methods, there is no reason to apply care that older adults resist to. The insights gained through this study, will help researchers and professional caregivers to develop such a multifactorial approach.